Jerome of Stridon: His Life, Writings and Legacy. Edited by Andrew Cain and Josef Lössl - Hunt, Thomas (The journal of theological studies, 2010)
It is an exciting time for those interested in the life and works of Jerome of Stridon. The last ten years have seen an efflorescence of scholarship on the choleric monk, priest, and exegete. It is appropriate, then, that this collection of essays should have arrived at the decade’s close, for it offers the reader both an assessment of the current state of the subject and various possibilities for new directions. The volume contains a collection of papers delivered at the conference of the same name, which took place in Cardiff during July 2006 . It contains 18 papers, and is divided into three sections. The majority of the papers are in English, although there are four in French.